The psoriatic non-lesional skin a battlefield of constant fight between susceptibility and protective factors - Kelemen Evelyn (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
In the last two decades, large-scale gene-expression studies on psoriatic skin samples revealed that even though non-lesional skin is macroscopically identical to healthy skin, it harbors several molecular differences. Originally, these molecular differences were thought to represent susceptibility factors for plaque formation. However, we review here several factors of immune regulation and structural alteration that are specific for the non-lesional skin and serve as protective factors by counteracting plaque formation and contributing to the maintenance of the non-lesional phenotype.